ANALISIS YURIDIS TERHADAP PENAGIHAN UTANG OLEH DEBT COLLECTOR BERDASARKAN (PJOK) NO 18/PJOK.01/2018 - PAKAYA, PUTRI REGINA S. (Ganec Swara, 2025)
This research aims to analyze the juridical aspects related to debt collection by debt collectors based on the Debt Collection Services Regulation (PJOK) No.18/PJOK.01/2018. The main focus of this research is to identify the legal position of debt collectors in the collection process as well as the legal consequences of debt arising from these collection actions. The method used in this research is a normative approach with qualitative analysis of primary, secondary, and tertiary legal sources.The results show that debt collectors act as collection agents who act under the authority of the creditor, but do not have permission to carry out forced execution without a court decision. Forced towing of motor vehicles by debt collectors can be considered an unlawful act if it does not follow established procedures, which can result in criminal liability for debt collectors in accordance with the provisions in the Criminal Code (KUHP).This study recommends the need for clearer and stricter regulations regarding debt collection practices by debt collectors to protect the rights of debtors and ensure that the collection process is carried out ethically and in accordance with applicable laws. Thus, it is hoped that a balance can be created between the interests of creditors and consumer protection in debt collection practices in Indonesia.